2006
DOI: 10.3758/bf03193435
|View full text |Cite
|
Sign up to set email alerts
|

When more is less: Negative exposure effects in unsupervised learning

Abstract: In this article, two broad classes of models of unsupervised learning are compared: correlation tracking models, according to which learning is expected to increase monotonically with exposure to instances, and category invention models, which can accommodate specific violations of monotonicity (negative exposure effects). In two experiments, increasing the number of training instances had a negative rather than a positive effect on unsupervised learning, a clear violation of monotonicity. The results of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 31 publications
1
36
2
Order By: Relevance
“…Order effects have been extensively studied in category learning (e.g., Clapper, 2006;Medin & Bettger, 1994;Zaki & Homa, 1999). In fact, rational models have been developed to account for the effects of category drift (i.e., recency effects) for autocorrelated environments that change over time (Elliott & Anderson, 1995).…”
Section: Figure 1 the Design Of Experiments 1 Dark Triangles (L1-l6 mentioning
confidence: 99%
“…Order effects have been extensively studied in category learning (e.g., Clapper, 2006;Medin & Bettger, 1994;Zaki & Homa, 1999). In fact, rational models have been developed to account for the effects of category drift (i.e., recency effects) for autocorrelated environments that change over time (Elliott & Anderson, 1995).…”
Section: Figure 1 the Design Of Experiments 1 Dark Triangles (L1-l6 mentioning
confidence: 99%
“…This article investigates the effects of different training sequences on subsequent category formation when an underlying category structure exists. Sequencing (order) effects have been shown to affect both intentional supervised category learning (Goldstone, 1996; Jones, Love, & Maddox, 2006; Jones & Sieck, 2003; Stewart, Brown, & Chater, 2002) and unsupervised incidental category learning (Clapper, 2006; Clapper & Bower, 1994, 2002). However, very little is known about their effects on unsupervised intentional category learning, an everyday form of categorization.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing (order) effects have been shown to affect both supervised and (incidental) unsupervised learning. While existing studies of supervised category learning addressed primarily the question of how contrast of successive stimuli affects the category assignment for the current stimulus with respect to its usual category assignment (Jones, Love, & Maddox, 2006; Jones & Sieck, 2003; Stewart, Brown, & Chater, 2002), studies of unsupervised learning addressed the question of whether the underlying category structure itself can be learned under particular exemplar sequences (Clapper, 2006; Clapper & Bower, 1994, 2002). As we also aim to address the question of category learnability under unsupervised learning, we first turn to the studies of unsupervised learning…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of a distinct "failure event" means that the leamer is trapped in an overaggregated state in which he or she remains persistently blind to the correlational stmcture of the set. Previous studies have shown strong evidence for this kind of aggregation effect (Clapper, 2006).…”
Section: The Category Invention Theory Of Unsupervised Learningmentioning
confidence: 97%